EVALUASI PROGRAM PELATIHAN MUSIK DI PONTIANAK - Gery, Gregorius; Mering, Aloysius; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to: 1. Address the problem of reduce training participants in the music training program at GBI. 2. Know the level of success and quality of the ongoing training program through meansurement through goal oriented questionnaire data. This research method is in the form of an evaluation, so that in the data processing this evaluation research uses qualitative and quantitative methods with an evaluation approach that is used by objective based evaluation developed by Ralp W Tyler in 1960. The results of this research, the music department of GBI Elshaddai needs to improve the training program at the input stage and through meansurements from the questionnaire data for the purpose of music training, the researchers obtained the success rate of achieving the GBI music training program by 93%, means that the level of attainment of the high training program objectives and the strength of the training program was very high. So the researchers suggest that, the music department of GBI should improve the input stage of the music training program, hold music training seminars to other Chruces..Keywords: Evaluation, Program Evaluation, Music Trainning.